2013
DOI: 10.1063/1.4826092
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced surface mobility and quantum oscillations in topological insulator Bi1.5Sb0.5Te1.7Se1.3 nanoflakes

Abstract: In this study, a series of Bi1.5Sb0.5Te1.7Se1.3 (BSTS) flakes 80-nm to 140-μm in thickness was fabricated to investigate their metallic surface states. We report the observation of surface-dominated transport in these topological insulator BSTS nanoflakes. The achievement of surface-dominated transport can be attributed to high surface mobility (∼3000 cm2/V s) and low bulk mobility (12 cm2/V s). Up to 90% of the total conductance, the surface channel was estimated based on the thickness dependence of electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(42 reference statements)
2
12
1
Order By: Relevance
“…This is different from the reported result that the sheet conductance is independent of the thickness in 2D TMDs 29 . These results support that other sources contribute to the measured conductivity in addition to the layer transport carriers 21 . We propose that these characteristics originate from the peculiar band structure of the topological insulator, and the observed thickness-dependent sheet conductance originates from the combination of the surface state and the bulk state.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This is different from the reported result that the sheet conductance is independent of the thickness in 2D TMDs 29 . These results support that other sources contribute to the measured conductivity in addition to the layer transport carriers 21 . We propose that these characteristics originate from the peculiar band structure of the topological insulator, and the observed thickness-dependent sheet conductance originates from the combination of the surface state and the bulk state.…”
Section: Resultssupporting
confidence: 81%
“…The extracted G s  = 8.7 (e 2 /h) and σ b  = 2.76 × 10 −2 (e 2 /h) nm −1 . σ b is larger than the reported value in the Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 topological insulator nanoflake by a factor of 5 21 .
Figure 2The inset shows the conductivity as a function of thickness in a log-log plot. The conductance decreases as the thickness increases.
…”
Section: Resultsmentioning
confidence: 81%
“…In table 2 we have collected the fit parameters ϕ l and α, as well as those obtained for BSTS nanoflakes reported in the recent literature. Hsiung et al [37] measured a flake with enhanced surface mobility and reported an α-value close to −1 as well. The α-values reported by Xia et al [32] obtained on a relatively thick nanoflake are systematically smaller than −1.…”
Section: Weak Antilocalizationmentioning
confidence: 78%
“…Therefore, the SdH effect in TIs has received ample attention in the literature, notably through experiments carried out on bulk crystals of Bi 2 Te 3 , Bi 2 Se 3 and Bi 2 Te 2 Se [12,11,26,27,28]. In addition, the SdH effect was reported for nonstochiometric BSTS (x, y)=(0.50,1.3) bulk crystals [29] and nanoflakes [30]. In most cases, the phase offset of the quantum oscillations obtained from a linear Landau level plot has been interpreted as a finite Berry phase.…”
Section: Introductionmentioning
confidence: 99%